2013
DOI: 10.2147/ott.s51532
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and disease-free survival in endometrial cancer: prognostic factors in 276 patients

Abstract: ObjectiveThe aim of the study reported here was to assess the disease-free survival and overall survival of patients with endometrial cancer and to determine independent factors affecting the prognosis.Materials and methodsThis was a retrospective study of a single-center clinical series of 276 patients (mean age 64 years) with histologically confirmed cancer of the corpus uteri. The standard treatments were extrafascial total hysterectomy and bilateral salpingo-oophorectomy with selective pelvic/para-aortic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 25 publications
7
31
1
Order By: Relevance
“…However, another study by Sonoda et al [31], reported a strong and positive correlation between tumor RCAS1 immunoreactivity and patient age. Patients' age is in general regarded as a negative prognostic factor in endometrial cancer [34,35]. Our results confirm this observation, because advanced age was associated with shortened survival.…”
Section: Discussionsupporting
confidence: 86%
“…However, another study by Sonoda et al [31], reported a strong and positive correlation between tumor RCAS1 immunoreactivity and patient age. Patients' age is in general regarded as a negative prognostic factor in endometrial cancer [34,35]. Our results confirm this observation, because advanced age was associated with shortened survival.…”
Section: Discussionsupporting
confidence: 86%
“…However, the median survival in our study is lower than the medial survival reported in Thailand in 2010 (14) and higher than that reported in Madrid, Spain in 2013 (15). Several prognostic factors have been shown to be predictors of survival in patients with endometrial cancer.…”
Section: Methodscontrasting
confidence: 78%
“… 20 Disease-free survival has been shown to be 91% in FIGO stage I patients and 52.5% in those with FIGO stage II, III and IV. 21 In the study by Garg et al ., survival in patients with stage I endometrioid adenocarcinoma with positive peritoneal washings was significantly poorer than in patients with negative peritoneal washings (88.2% vs . 98.6%).…”
Section: Discussionmentioning
confidence: 97%